Experimental investigation of water uptakes under static and dynamic conditions for cooling application - Leong, Zheng Kang (2019)
The amount of uptake – offtake difference is an important factor for the design of cooling systems. Adsorption cooling depends on the acquiescence of the adsorbent properties. The material needs to be insoluble in the mixture, exhibit stability upon exposure to oxygen, moisture, temperature and has suitable pore size for uptake and offtake. In recent years, Metal Organic Frameworks (MOFs) have been identified as a promising material to yield crystals of well-defined porosity, high chemical and thermal stability. This project presents the water adsorption on Aluminium fumarate (AlFum) and Zirconium based MOFs (MOF-801), for temperatures ranging from 25˚C to 60˚C and pressures up to saturated condition (P/Ps => 1). The experimental result revealed that adding methyl group (CH3) into AlFum and MOF-801 could enhance the efficiency of the adsorbent. It is found that CH3-AlFum has better water uptake rates as compared to AlFum, while (CH3)2-MOF-801 shows faster kinetics as compared to the parent MOF-801. A gravimeter analyser is used to measure water uptakes and kinetics. It is found that the modified AlFum and MOF-801 showed better performance in term of uptake-offtake different (Δq), which are 10.6% and 33.3% higher respectively as compared with the base materials. Employing Thermogravimetry analysis (TGA) and Differential scanning calorimetry (DSC) the desorption enthalpy and the specific heat are measured. It is found that the modified MOFs show a decrease in enthalpy change compared to the base form MOFs. The result demonstrates high potential working pair of having CH3 in the MOFs. CH3-linked Aluminium fumarate and MOF-801 adsorbents are suitable for the design of adsorption bed.